INOVASI FINANSIAL DALAM MENINGKATKAN KUALITAS PENDIDIKAN MELALUI MANAJEMEN KEUANGAN DI SDN KRANGGOT - Raman, Raman; Yusuf, Furtasan Ali; Hayadi, B. Herawan; Rahmulyana, Anjar; Yustiva, Fitriyatul; Junaesih, R. (Bhinneka Multidisiplin Journal, 2024)
This research explores the impact of financial innovation on the quality of education through financial management at SDN Kranggot. Based on data from interviews, observations, and document analysis, the main findings include the implementation of financial innovations such as digital financial systems, project fund management, and community involvement. This innovation has increased the efficiency and transparency of school financial management. Better fund management has supported the provision of better educational facilities, teacher training, and the provision of learning materials. Parental and local community involvement has also increased, contributing to the raising of additional funds and increasing accountability in the management of school funds. However, challenges such as limited resources and technical skills require solutions such as staff training. This research highlights the importance of financial innovation in improving the quality of education, while emphasizing the need for investment in capacity development to address emerging challenges